Factors Influencing Student Learning Outcomes: Teacher Competence, Learning Environment, and Learning Stress - Bayhaqi, Hasmi Nur; Darmawan, Didit (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2025)
The level of progress of a nation significantly depends on the quality of education, which is reflected in the success of the learning process. Teachers, the learning environment, and students' internal conditions are among the primary factors contributing to the success of the learning process. This study aims to determine the significant influence of teacher competence, the learning environment, and academic stress on the academic performance of students at MTs Bi’rul Ulum, Gemurung, Gedangan, Sidoarjo. The research employed a quantitative survey method with a population of 115 students, all of whom were included as samples using a total sampling technique. The data were analyzed using multiple regression analysis. The findings of this study revealed that teacher competence has a significant positive effect on students' academic performance, the learning environment was found to have an insignificant effect, while academic stress showed a significant influence on students' academic performance at MTs Bi’rul Ulum, Gemurung, Sidoarjo. The contribution of this research enriches the discourse on education by examining the impact of teacher competence, learning environment, and academic stress on student performance in the context of Islamic junior high school setting, which has not been extensively discussed in the previous literature.